Thermosolutal Marangoni convection of Bingham non-Newtonian fluids within inclined lid-driven enclosures full of porous media - Ahmed, Sameh E.; Öztop, Hakan Fehmi; Elshehabey, Hillal M. (Wiley, 2021)
Multiconvection modes together with the entropy generation due to Marangoni effects, movement of the side walls, and double-diffusive convection within lid-driven enclosures filled by a porous medium are examined. The current flow domain is an inclined non-Darcy porous geometry having a top free surface where linear expressions in terms of the temperature and concentration are presented for the surface tension. The dynamic viscosity of the suspension has an exponential profile and the convective boundary conditions are taken into account. The finite volume method in which values of the pressure are computed using the SIMPLE algorithm is applied to solve the governing system. The non-Newtonian Bingham fluids are applied for different governing parameters, such as Grashof number, Reynolds number, Marangoni number, Darcy number, inclination angle of the cavity, Biot number, Bingham number, and geometrical parameters. It is observed that a rise in the Bingham number from 0 to 0.5 causes a decrease in the average Bejan number up to 4.77%. Also, the averaged and mixing temperatures are augmented as the inclination angle is altered, regardless values of the Biot number.
Keywords: entropy; lid-driven enclosure; Marangoni effects; mixed convection; porous medium